Management Information System at Hume Cemboard Fibre Cement Division - Subramaniam, Vickneswaran (1997)
This case study is about Hume Cemboard Fibre Cement Division which is facing problems of poor information flow system and high staff turnover. A few scenarios and operations in each department has been used to describe the problem. The alternatives are : 1) Hire more staff 2) Develop a Management Information System and motivate current staff Developing a Management Information System and motivating the current staff has been proposed to overcome the problem.